2013
DOI: 10.1186/1472-6750-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Fibres from flax overproducing β-1,3-glucanase show increased accumulation of pectin and phenolics and thus higher antioxidant capacity

Abstract: BackgroundRecently, in order to improve the resistance of flax plants to pathogen infection, transgenic flax that overproduces β-1,3-glucanase was created. β-1,3-glucanase is a PR protein that hydrolyses the β-glucans, which are a major component of the cell wall in many groups of fungi. For this study, we used fourth-generation field-cultivated plants of the Fusarium -resistant transgenic line B14 to evaluate how overexpression of the β-1,3-glucanase gene influences the quantity, quality and composition of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 61 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…This is a tricky and time-consuming process; therefore not many studies have been reported on this subject. So far, some modifications were done to obtain better quality fiber in flax; moreover, first report on the properties and applications of the fiber from such modified plants have already been published (Preisner et al, 2014a;Skórkowska-Telichowska et al, 2011;Wojtasik et al, 2013;Wróbel-Kwiatkowska et al, 2007b).…”
Section: Application Of Genetic Engineeringmentioning
confidence: 98%
See 2 more Smart Citations
“…This is a tricky and time-consuming process; therefore not many studies have been reported on this subject. So far, some modifications were done to obtain better quality fiber in flax; moreover, first report on the properties and applications of the fiber from such modified plants have already been published (Preisner et al, 2014a;Skórkowska-Telichowska et al, 2011;Wojtasik et al, 2013;Wróbel-Kwiatkowska et al, 2007b).…”
Section: Application Of Genetic Engineeringmentioning
confidence: 98%
“…The most commonly used method to introduce DNA fragments into plant genome is an Agrobacterium method, which is widely used also to improve fibrous plants productivity and quality (Day et al, 2009;Roach et al, 2011;Wahby et al, 2013;Wang et al, 2008;Wojtasik et al, 2013;Wróbel-Kwiatkowska et al, 2007a;Wróbel et al, 2004).…”
Section: Alternative Genome Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A target characteristic of the plant cell wall should be a high cellulose content and crystallinity, low level of lignification and cross linking [328]. Limiting lignin-hemicellulose-cellulose network linkages by modifying lignin content [329,330], pectin methylation [331], fucosyl substitution of xyloglucan [332,333], [Me]GlcA and acetylation substitution of xylan [334] or ferulic acid substitution of xylan [133] are other potential molecular targets for fibre modification. On the other hand, a high hemicellulose content is correlated with higher nanofibrillation of fibres and individualization of the microfibrils [335].…”
Section: Fibre Improvementmentioning
confidence: 99%
“…Identically, LorencKukula et al (2007) transformed flax with the aim of improving resistance to Fusarium. Wojtasik et al (2013) analysed the biochemical composition of GM flax fibres overexpressing the β-1,3-glucanase gene, they accentuated their improved mechanical properties and increased antioxidant potential supporting their biomedical applications. Chen et al (2008) focused on pyramiding of alleles with different rust resistance specificity in transgenic flax and creation of flax lines with multiple resistance characteristics.…”
Section: Agronomic Traitsmentioning
confidence: 99%